2017
DOI: 10.1007/s40123-017-0079-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Botulinum Toxin A Injection and Lacrimal Punctal Plugs for the Control of Post-LASIK Dry Eye Manifestations: A Prospective Study

Abstract: IntroductionLaser in situ keratomelieusis (LASIK) is one of the commonest refractive procedures performed nowadays. The dry eye problem is nearly universal in all patients after LASIK and it can be so annoying that the post-operative patient satisfaction is sometimes precluded. Conventional treatment includes the use of artificial tears. Alternative methods such as punctal plugs and botulinum toxin injection can be used for the management of post-LASIK dry eye. The aim of this study is to compare botulinum tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…Compared to the punctal plug group, patients receiving 3.3 U of Botox ® injected into the medial lower eyelids had higher overall satisfaction (100%) and a lower complication rate (16.7%). Following this study, Fouda et al [ 57 ] demonstrated similar findings for the treatment of patients with dry eye after laser in situ keratomileusis (LASIK) surgery. Sixty patients were randomly and equally assigned to one of three groups comprising the control (i.e., topical lubricants only), BoNT, and punctal plug (i.e., temporary silicone plugs in the lower puncta) groups.…”
Section: Dry Eye Improvement: Bont Decreases Lacrimal Drainagesupporting
confidence: 68%
See 1 more Smart Citation
“…Compared to the punctal plug group, patients receiving 3.3 U of Botox ® injected into the medial lower eyelids had higher overall satisfaction (100%) and a lower complication rate (16.7%). Following this study, Fouda et al [ 57 ] demonstrated similar findings for the treatment of patients with dry eye after laser in situ keratomileusis (LASIK) surgery. Sixty patients were randomly and equally assigned to one of three groups comprising the control (i.e., topical lubricants only), BoNT, and punctal plug (i.e., temporary silicone plugs in the lower puncta) groups.…”
Section: Dry Eye Improvement: Bont Decreases Lacrimal Drainagesupporting
confidence: 68%
“…Subsequently, a few researchers have studied the efficacy and safety of BoNT-A injection into the medial eyelids [ 53 , 54 , 55 , 56 , 57 , 58 ]. Sahlin et al [ 53 ] found the injection of BoNT-A into the medial lower eyelid reduced lacrimal pump and decreased ocular discomfort in a patient with Sjogren’s syndrome.…”
Section: Dry Eye Improvement: Bont Decreases Lacrimal Drainagementioning
confidence: 99%
“…As mentioned above, previous studies have shown inconsistent results of the Schirmer test [ 5 , 8 , 9 , 10 , 15 , 16 , 17 ]. The studies in which the injection sites were limited to the medial side of lower and upper eyelids have shown increased Schirmer test values [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 96%
“…Several treatments, such as artificial tears, punctal plugs, and botulinum toxin, have been used to treat dry eye syndrome after LASIK surgery. However, these therapies are associated with some complications, including eye irritation, extrusion, or decreasing blinking power [24]. …”
Section: Discussionmentioning
confidence: 99%